Ocorrência de acidente do trabalho por material perfurocortante entre trabalhadores de enfermagem de um hospital universitário da cidade de Campinas, estado de São Paulo Accidents with perforative tools among nursing workers - Simone Brandi; Maria Cecília Cardoso Benatti; Neusa Maria Costa Alexandre (SciELO, 1998)
Com o objetivo de estudar aspectos da ocorrência de acidente do trabalho por material perfurocortante entre trabalhadores de enfermagem de um hospital universitário, foram entrevistados 46 trabalhadores que se acidentaram no período de junho a dezembro de 1994. Os resultados forneceram dados importantes que poderão subsidiar programas de prevenção. This study has the objective to evaluate certain aspects of the occurrence of accidents of work with perforative cutting tool in nursing workers of a university hospital. Forty-six workers who had accidental needlesticks and injuries from other sharp objects (from. June to /December 1994) were interviewed. The data found are likély to help programs of preventio of accidents with nursing workers.